Produtividade da soja em função da aplicação de fertilizantes comerciais formulados com diferentes fontes de zinco e fitodisponibilidade dos metais pesados tóxicos cádmio, chumbo e cromo - Nava, Ivair André (2008)
The Brazilian agriculture, covering the cultivation of soybeans (Glycine max L.), is going through a phase in which the pursuit of maximum productivity is of fundamental importance. The objective of this work is to evaluate the productivity and yield components of soybeans, with the application of fertilizers formulated with different sources of Zn and phytoavailability poisonous heavy metals Cd, Pb and Cr for this culture. The experimental design was in the form of randomized (BDC) in factorial [(5x2) + 1], with three replicates. The treatments consisted of five sources of fertilizer, two doses of fertilizer and a witness. The fertilizer has the formula of NPK (2-20-18) with 0.3% of Zn in the form of granules, applied at the base. We used five sources of fertilizer: NPK made source of Zn + Brand A; made NPK + Zn source of the mark B; made NPK + Zn source of the mark C; made NPK + Zn source of the mark D; NPK made without Zn in the mixture. Will be considered following doses of fertilizer: once the recommendation of fertilizer (NPK + Zn) for the soybean crop and twice the recommendation of fertilization. The witness is characterized by not contain the basic fertilizer. There were certain toxic heavy metals (Cd, Pb and Cr) and nutrients (P, K, Ca, Mg and Zn) in the structure of the soybean plant and evaluation of the components of output and productivity in each plot useful (2.7 m2) in kg ha-1. After harvest, within each parcel useful, soil samples were collected for determination of macro-and micronutrients. All data obtained experimentally were subjected to analysis of variance and the averages compared by Tukey test at 5% probability. For the field conditions, where the experiment was conducted and based on the results obtained, the following conclusions were reached: The application of twice the recommended dose provided the average elevation of the components of output and productivity as well as the levels of P, K, Zn and Cr in soil. The implementation of the recommended dose has increased medium, the levels of leaf Ca, Zn, Pb, Cr and the levels of Mg, Cd and Pb in soil, for use twice the recommended dose